Peran Chatbot dalam Membentuk Interaksi Sosial, Fandom, dan Identitas Pengguna di Media Sosial (International Forum of Researchers and Lecturers, 2024)
The rapid development of artificial intelligence has encouraged the widespread use of chatbots on social media platforms, transforming patterns of digital communication and interaction. This study aims to examine the role of chatbots in shaping social interaction, fandom dynamics, and users’ digital identities within contemporary online culture. The research employs a literature review approach using grounded theory as an analytical framework to identify patterns, themes, and emerging concepts from relevant academic publications published between 2021 and 2025. Articles were collected through academic databases and systematically selected based on predefined inclusion and exclusion criteria. The findings indicate that chatbots have shifted from being purely functional technological tools to becoming cultural actors that influence emotional engagement, community formation, and identity expression in digital spaces. Chatbots contribute to creating perceived emotional closeness, strengthening fandom interactions, and facilitating self-expression, particularly within popular culture and creative industries. However, the study also highlights several challenges, including emotional dependency, algorithm-driven homogenization of preferences, gender bias, and aggressive behavior in human–machine interactions. Cultural context plays a significant role in shaping user acceptance and interpretation of chatbots. These findings imply that chatbot development and implementation should consider not only technical efficiency but also social, psychological, and ethical dimensions to ensure responsible and inclusive digital interaction.